Measurement assurance testing of technical systems in order to re-value the duration of their life cycle - Куц, Ю. В.; Реуцький, Є. А.; Щербак, Л. М. (Problems of Informatization and Control, 2011)
The tasks of tests of the technical systems are considered, the conditional model of life cycle of the technical system is resulted with the use of computer measuring experiment between the stages of making and exploitation, grounded his efficiency and necessity at creation of the metrology providing